Abandon “Race.” Focus on Racism - Braveman, Paula; Parker Dominguez, Tyan (Frontiers in Public Health, 2021)
The concept of “race” emerged in the 1600s with the trans-Atlantic slave trade, justifying slavery; it has been used to justify exploitation, denigration and decimation. Since then, despite contrary scientific evidence, a deeply-rooted belief has taken hold that “race,” indicated by, e.g., skin color or facial features, reflects fundamental biological differences. We propose that the term "race" be abandoned, substituting “ethnic group” while retaining “racism,” with the goal of dismantling it. Despite scientific consensus that “race” is a social construct, in official U.S. classifications, “Hispanic”/”Latino” is an “ethnicity” while African American/Black, American Indian/Alaska Native, Asian/Pacific Islander, and European American/White are “races.” There is no scientific basis for this. Each grouping reflects ancestry in a particular continent/region and shared history, e.g., the genocide and expropriation of Indigenous peoples; African Americans’ enslavement, oppression and ongoing disenfranchisement; Latin America’s Indigenous roots and colonization. Given migrations over millennia, each group reflects extensive genetic admixture across and within continents/regions. “Ethnicity” evokes social characteristics such as history, language, beliefs, customs. “Race” reinforces notions of inherent biological differences based on physical appearance. While not useful as a biological category, geographic ancestry is a key social category for monitoring and addressing health inequities because of racism’s profound influence on health and well-being. We must continue to collect and analyze data on the population groups that have been racialized into socially constructed categories called “races.” We must not, however, continue to use that term; it is not the only obstacle to dismantling racism, but it is a significant one.